Experimental and Finite Element Investigation of Thermal Distribution and Heat Flux in an Internal Combustion Engine Cylinder - IWERIOLOR, Sunday; EMORDI, Ngozi G.; ISAAC, Festus O.; CHUKWUKA, Linus; AKPENYI-ABOH, Onyekachukwu N.; ANWULE, Liberty (FUDMA Journal of Engineering and Technology, 2026)
The radial temperature variation, heat flow, heat-transfer rate, and convective cooling pattern within an engine cylinder wall were all examined using experimental and finite-element methods. At particular points along the cylinder wall, radial temperature measurements were taken from the inner combustion surface. The simulated temperatures resulting from steady-state finite-element thermal analysis were compared with experimental data. Experimented temperature data displayed a steady temperature drop from 450 °C at the inner wall to 158 °C at the exterior wall. Errors margins of 0.50 °C, 11.48 °C, and 3.13 °C were observed as simulated temperatures nearly approximate to interpolated experimental data. A maximum total heat flow of 5.415 × 10² W/m² became apparent via Temperature Contour analysis, resulting to a simulated heat-transfer rate of 146 kW.This is consistent with the experimental figure of 147 kW (0.68% deviation). The experimental result of 1100 W/m²•K differs 1.8% from the estimated convective heat-transfer coefficient of 1080 W/m²•K. The remarkable correlation between the observed and simulated temperatures, heat flux, heat-transfer rate, and convective coefficient indicates that the well-established finite-element framework provides a reliable and experimentally validated technique for quantifying heat transfer in engine cylinders. This provides a strong basis for the development of improved coatings, high-temperature-resistant materials, and cooling techniques in the future as well as a verifiable technique for establishing engine cylinder performance, durability, and thermal variables.
Keywords: Thermal Analysis, Engine Cylinder, Temperature, Finite Element, Heat transfer.